ANALISIS PERHATIAN ORANG TUA SELAMA PEMBELAJARAN DARING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Fatmala, Shofi; Bintoro, Henry Suryo; Ardianti, Sekar Dwi (Jurnal Ilmiah Bina Edukasi, 2021)
online learning, factors that affect parents attention and the role of parents attention to students mathematical comprehention skills. This research uses data collection techniques in the form of observations, interviews, and documentation. Data analysis used in this research is qualitative descriptive data analysis. In this study, it was found that, 1) where most of parents pay attention to stundent, 2) The factors that affect the attention of parents are, (a) the presence of desire / need, (b) strong lack of stimulus, (c) busy activities / work, (d) physical condition, (e) mental and surrounding atmosphere, (f) the educational ability of parents. 3) Students have sufficient mathematical comprehention skills. Parents attention is only one of the factors that affect students mathematical comprehention skills, another factor is the existence of internal factors and external factors.